A method for producing high-performance lithium-ion power batteries using cobalt sulfate

Through a multi-step cobalt sulfate production method, the problem of the great impact of traditional processes on the environment is solved, and the production of high-performance cobalt sulfate and zero wastewater discharge is achieved. It is suitable for high-performance lithium-ion power batteries and has significant economic benefits and environmental value.

CN115057481BActive Publication Date: 2025-03-18YUNNAN JINXUN ELECTRONIC COMMERCE CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202210644113.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-06-09
Publication Date
2025-03-18
Estimated Expiration
2042-06-09

AI Technical Summary

Technical Problem

The traditional industrial cobalt sulfate production process has a great impact on the environment, and it fails to effectively utilize valuable metal by-products, which cannot meet the quality needs of high-performance lithium-ion power batteries.

Method used

A high-performance lithium-ion power battery is used to produce cobalt sulfate, including slurry, acid leaching, reduction leaching, filtration, precipitation, extraction, ion exchange, reverse osmosis, MVR evaporation and crystallization, and the zero emission of wastewater and valuable metal resources are achieved by recycling products and by-products.

Benefits of technology

The production of high-performance cobalt sulfate has been achieved. The products are mainly low in TOC, oil, water insoluble matter and magnetic foreign matter. The impurities meet the requirements of the ROHS, REACH and HF directives. They are suitable for high-performance lithium-ion power battery precursor materials, with significant economic benefits and environmental value.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115057481B_ABST
    Figure CN115057481B_ABST
Patent Text Reader

Abstract

The present invention provides a method for producing high-performance lithium-ion power batteries using cobalt sulfate, comprising the steps of adding water to crude cobalt hydroxide and stirring to obtain a slurry; pumping the slurry into a leaching tank for reduction leaching, performing pressure filtration after the leaching is completed, performing countercurrent washing on the filter residue, and analyzing the pH value and Fe content of the leaching solution in the filtrate. 2+ Concentration, based on Fe 2+ The concentration is oxidized, neutralized and precipitated to remove iron; the iron-removed liquid is extracted and impurities are removed by P204, cobalt is extracted by P507 and separated from nickel and magnesium to obtain a cobalt sulfate solution, the P507 raffinate is evaporated and crystallized to produce ammonium magnesium sulfate, the cobalt sulfate solution is deoiled and demagnetized, and MVR is evaporated and crystallized to obtain high-performance lithium-ion power battery cobalt sulfate. The high-performance lithium-ion power battery produced by using cobalt sulfate in the present invention improves leaching, extraction and other processes compared to traditional industrial cobalt sulfate production, greatly reduces the use of raw materials and the impact on the environment, and can obtain ammonium magnesium sulfate as a by-product in the production process to improve economic benefits.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of cobalt sulfate production technology, and specifically relates to a method for producing cobalt sulfate for high-performance lithium-ion power batteries. Background Art

[0002] Cobalt sulfate was originally mainly used in the fields of ceramics and chemicals. In 2015, it began to tilt towards lithium batteries with high specific energy. After 2017, ternary lithium batteries and production technologies became the mainstream of research in the industry, and the demand for cobalt sulfate used in high-performance lithium-ion power batteries increased significantly. At present, my country's cobalt sulfate raw material industry continues to improve the refining process and increase production capacity in line with the market demand for ternary positive electrode materials. With the increase in the volume of ternary batteries for new energy vehicles, the cobalt sulfate raw material industry will release greater room for growth in the future. Traditional industrial cobalt sulfate production, leaching, extraction and other processes have a greater impact on the environment, and the emission of harmful gases such as sodium pyrosulfite or sulfur dioxide gas increases. Traditional processes do not use valuable metals to produce by-products, and the quality of the finished cobalt sulfate cannot meet the use requirements of high-performance lithium-ion power batteries. Therefore, the present invention proposes a method for producing cobalt sulfate for high-performance lithium-ion power batteries. Summary of the invention

[0003] In order to overcome the problems in the background technology, the present invention provides a method for producing a high-performance lithium-ion power battery using cobalt sulfate.

[0004] To achieve the above object, the present invention is implemented through the following technical solutions:

[0005] A method for producing high-performance lithium-ion power batteries using cobalt sulfate comprises the following steps:

[0006] (1) adding distilled water, industrial water and crude cobalt hydroxide into a slurry tank and stirring to obtain a slurry;

[0007] (2) The slurry is pumped into a leaching tank, sulfuric acid is first added and the pH is controlled to carry out an acid leaching reaction, and then hydrogen peroxide is added for reduction leaching. If the leaching reaction is not complete, a small amount of sodium sulfite is added. After the leaching is completed, filter pressing is performed to obtain leaching residue and leaching filtrate. The leaching residue is countercurrently washed three times, and the filtrate after washing is returned to the leaching step. The filter residue after washing is sent out for treatment and toxicity detection;

[0008] (3) Analysis of pH and Fe in leachate 2+ Concentration, based on Fe 2+ Add oxidants such as hydrogen peroxide, sodium hypochlorite, and sodium chlorate to Fe 2+ Oxidized to Fe 3+, then adding a neutralizing agent, ammonium bicarbonate or the crude cobalt hydroxide slurry prepared in step (1), adjusting the pH to carry out a precipitation reaction, and after precipitation, filtering to obtain iron-removing slag and iron-removing liquid, and the iron-removing slag is returned to the leaching section of step (2);

[0009] (4) The pH of the liquid after iron removal is adjusted, and the liquid is extracted and impurities are removed by P204. P204 is saponified with ammonia water. The P204 raffinate is separated from cobalt and nickel and magnesium by P507. P507 is saponified with ammonia water. The organic phase loaded with P507 is stripped with sulfuric acid to obtain a cobalt sulfate solution.

[0010] (5) The P507 raffinate is subjected to ion exchange to remove impurities, secondary reverse osmosis membrane separation and evaporation crystallization to produce ammonium magnesium sulfate, and the distilled water evaporated from the P507 raffinate is returned to the slurry section of step (1), with zero wastewater discharge;

[0011] (6) Degreasing graphene with cobalt sulfate solution and demagnetizing with a demagnetizer;

[0012] (7) The demagnetized cobalt sulfate solution is mixed with the evaporation mother liquor and then subjected to MVR evaporation crystallization;

[0013] (8) The evaporated cobalt sulfate concentrate is poured into a crystallization kettle for cooling and crystallization. After cooling and crystallization, centrifugation is started. The centrifuged mother liquor is finely filtered and deoiled by graphene and then returned to the MVR evaporation and crystallization step to continue evaporation and crystallization. The centrifuged material is cobalt sulfate.

[0014] Furthermore, in step (1), the solid-liquid ratio is 1:1.5-2.

[0015] Furthermore, in step (2), the leaching acid is 98% sulfuric acid, the pH value is controlled at 1.0-1.5 during the acid leaching reaction, the reaction temperature is 50-60° C., the reaction time is 0.5-1h, and the reducing agent for reduction leaching is 27.5% hydrogen peroxide. The unit consumption of hydrogen peroxide is controlled at 0.5-0.6 t / t. The Co content in the leaching solution is 60-80 g / l, and the total toxic substances in the leached residue are less than 0.1%.

[0016] Furthermore, the oxidation reaction temperature of the hydrogen peroxide and sodium hypochlorite in step (3) is 50-60°C, the pH value of the cobalt hydroxide slurry and ammonium bicarbonate is adjusted to 3.0-3.8, and the reaction is carried out for 0.5-1h. After the reaction, the solution Fe 全 <0.1g / l.

[0017] Furthermore, in step (4), the pH of the liquid after iron removal is adjusted to 2.5-3.5, the concentration of P204 is 24-28%, and it is diluted with sulfonated kerosene (concentration 72-76%). P204 is saponified with 20-25% ammonia water, and the saponification rate is controlled to 60-65%. The saponification rate of P507 is controlled to 60-65%, and the concentration of sulfuric acid stripping is 4.0-4.5 mol / l.

[0018] Furthermore, in step (5), the P507 raffinate is evaporated and crystallized to produce ammonium magnesium sulfate. First, the P507 raffinate is subjected to ZGD905 ion exchange resin to remove heavy metals such as nickel, cobalt, and copper, so that Ni is less than 0.5 mg / l, Co is less than 0.5 mg / l, and Cu is less than 0.5 mg / l; then reverse osmosis separation is performed, and the secondary reverse osmosis membrane concentration ratio is 4-6:1, and the salt content of the membrane separation purified water is less than 15 mg / l. Then, the evaporation is carried out into MVR evaporation and crystallization, the evaporation temperature is 75-90°C, the heat exchanger pressure is 450-600 mbar, and the material is discharged when the evaporation reaches a saturated solution.

[0019] Furthermore, in step (6), the cobalt sulfate solution is deoiled to an oil content of less than 10 mg / l, and is demagnetized to a magnetic foreign matter content of less than 20 PPb, and the magnetic force of the demagnetizer is greater than 12000 Gs.

[0020] Furthermore, in step (7), the feed flow rate of the MVR evaporation crystallization is 6-15 m3 / h, the feed temperature is 65-80°C, the compressor temperature difference of the MVR evaporator during normal evaporation is ±12°C, the heat exchanger pressure is 350-600 mbar, and the evaporation density is 1.49-1.52 g / cm 3 Time discharge.

[0021] Furthermore, in step (8), the crystallization is cooled to 27-35°C and then centrifuged. The mother liquor is precisely filtered using a 1 μm filter element, and the mother liquor is deoiled to an oil content of ≤8 mg / l. The centrifuged cobalt sulfate is placed for 2-4 hours and then packaged.

[0022] Beneficial effects of the present invention:

[0023] This process processes the products of each section and returns the products to different steps of the process for recycling. The by-product ammonium magnesium sulfate can be used as a chemical raw material and fertilizer raw material to improve economic benefits, achieve zero wastewater discharge, and recycle valuable metal elements. The product has low TOC, oil, water-insoluble matter and magnetic foreign matter, and the impurities comply with the requirements of ROHS, REACH and HF directives. It can be used as a precursor raw material for high-performance lithium-ion power batteries. It is a clean production process with very significant economic benefits and environmental value. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 It is a process flow chart of the present invention. DETAILED DESCRIPTION

[0025] In order to make the objectives, technical solutions and beneficial effects of the present invention more clear, the preferred embodiments of the present invention will be described in detail below with reference to the accompanying drawings to facilitate understanding by technicians.

[0026] The present invention discloses a method for producing high-performance lithium-ion power batteries using cobalt sulfate. Figure 1 :A method for producing high-performance lithium-ion power batteries using cobalt sulfate comprises the following steps:

[0027] (1) Add distilled water, industrial water and crude cobalt hydroxide into a slurry tank at a solid-liquid ratio of 1:1.5-2, and stir to obtain a slurry.

[0028] (2) The slurry is pumped into the leaching tank. First, 98% sulfuric acid is added and the pH is controlled at 1.0-1.5. The reaction temperature is 50-60°C. The acid leaching reaction is carried out for 0.5-1h. Then, 27.5% hydrogen peroxide is added for reduction leaching. The unit consumption of hydrogen peroxide is controlled at 0.5-0.6t / t. If the leaching reaction is not complete, a small amount of sodium sulfite is added. After the leaching is completed, filter pressing is carried out to obtain leaching residue and leaching filtrate. The Co content in the leaching liquid is 60-80g / l. The leaching residue is countercurrent washed three times. The filtrate after washing is returned to the leaching step. The toxicity test of the washed filter residue is <0.1% and qualified. In the leaching process, the reducing agent is upgraded. The reduction is changed from sodium metabisulfite or sulfur dioxide gas to hydrogen peroxide combined with a small amount of sodium metabisulfite, which reduces the emission of sulfur dioxide and hydrogen sulfide gas.

[0029] (3) Analysis of pH and Fe in leachate 2+ concentration, heated to 50-60°C, based on Fe 2+ Add oxidants such as hydrogen peroxide, sodium hypochlorite, and sodium chlorate to Fe 2+ Oxidized to Fe 3+ Then, add the neutralizing agent ammonium bicarbonate or the crude cobalt hydroxide slurry prepared in step (1), adjust the pH to 3.0-3.8 to carry out precipitation reaction, react for 0.5-1h, and filter press to obtain iron-removing slag and iron-removing liquid after precipitation, Fe 全 If the concentration is less than 0.1 g / l, the iron-removing slag is returned to the leaching section of step (2); for low-temperature iron removal, crude cobalt hydroxide slurry or ammonium bicarbonate is used to adjust the pH, eliminating the use of soda ash and reducing steam consumption.

[0030] (4) The pH of the solution after iron removal is adjusted to 2.5-3.5, and impurities are removed by extraction with P204 (P204 concentration is 24-28%, sulfonated kerosene concentration is 72-76%). P204 is saponified with 20-25% ammonia water, and the conversion rate is controlled at 60-65%. The P204 raffinate is separated from cobalt and nickel and magnesium by P507. P507 is saponified with ammonia water, and the conversion rate is controlled at 60-65%. The organic phase loaded with P507 is stripped with 4.0-4.5 mol / l sulfuric acid to obtain a cobalt sulfate solution, Co: 105-130 g / l; Ni ≤ 0.005 g / l; Na ≤ 0.005 g / l; Cu ≤ 0.003 g / l; Fe ≤ 0.002 g / l; Cr ≤ 0.002 g / l; Cl ≤ 0.05 g / l; Zn ≤ 0.001 g / l; Cd ≤ 0.005 g / l; Mg≤0.008 g / l; Ca≤0.01 g / l.

[0031] (5) The P507 raffinate is subjected to ZGD905 ion exchange resin to remove heavy metals such as nickel, cobalt and copper, so that Ni is less than 0.5 mg / l, Co is less than 0.5 mg / l and Cu is less than 0.5 mg / l. It is then separated by a secondary reverse osmosis membrane, and the secondary reverse osmosis membrane concentration ratio is 4-6:1. The salt content of the membrane separation purified water is less than 15 mg / l. It then enters the MVR evaporation crystallization to produce ammonium magnesium sulfate. The evaporation temperature is 75-90°C, and the heat exchanger pressure is 450-600 mbar. The material is discharged when the saturated solution is evaporated. The distilled water evaporated from the P507 raffinate is returned to the slurry stage of step (1). The extraction of the P507 raffinate is performed by ammonia saponification. The evaporation crystallization of the raffinate can obtain the by-product ammonium magnesium sulfate, which can be used as a chemical raw material and a fertilizer raw material to improve economic benefits while achieving zero wastewater discharge.

[0032] (6) Graphene is deoiled by cobalt sulfate solution, and the oil content is less than 10 mg / l. It is also demagnetized by a demagnetizer, and the magnetic foreign matter is less than 20 PPb. The magnetic force of the magnetic rod is greater than 12000 Gs.

[0033] (7) After demagnetization, the cobalt sulfate solution is mixed with the evaporation mother liquor and then subjected to MVR evaporation crystallization. The cobalt sulfate solution before evaporation is 100-150 g / L; Fe: ≤0.005 g / L; Cu≤0.007 g / L; Ca: ≤0.08 g / L; Mn≤0.008 g / L; Mg≤0.008 g / L; Na≤0.05 g / L; Cl≤0.9 g / L; Pb≤0.008 g / L; Cd: ≤0.04 g / L, oil content ≤10 mg / L; the feed flow rate of MVR evaporation crystallization is 6-15 m 3 / h, feed temperature is 65-80℃, the compressor temperature difference of MVR evaporator is ±12℃, the heat exchanger pressure is 350-600mbar, and the evaporation density is 1.49-1.52g / cm 3The material is discharged at the same time; MVR evaporation crystallization is adopted, and titanium is used for the contact between the equipment and the material. The deep purification precision filtration and graphene oil removal process reduce the oil and impurity content of the product.

[0034] (8) The evaporated cobalt sulfate concentrate is poured into a crystallization kettle for cooling and crystallization. After cooling to 27-35°C, centrifugation is started. The centrifuged mother liquor is subjected to precision filtration (1 μm filter element) and graphene deoiling. After the mother liquor oil content is ≤8 mg / l, it is returned to the MVR evaporation and crystallization step and evaporation and crystallization are continued. The centrifuged material is cobalt sulfate, which is placed for 2-4 hours before packaging. The obtained high-performance lithium-ion power battery uses cobalt sulfate, CO ≥ 20.50%; Ni ≤ 0.001%; ​​Fe ≤ 0.0005%; Cu ≤ 0.0005%; Ca ≤ 0.001%; ​​Mg ≤ 0.001%; ​​Cl ≤ 0.005%; Cd: ≤0.0005%; Cr≤0.0005%; Na≤0.0008%; Mn≤0.001%; ​​Pb≤0.0005%; Zn≤0.0005%, As≤0.0005%, Hg≤0.0005%; Al≤0.001%; ​​Si≤0.001%; ​​Li≤0.001%, K≤0.001%; ​​F≤0.002%; Water insoluble matter≤0.005%; pH: 4.5~6.5; TOC≤0.006%; Magnetic foreign matter≤80PPb, oil content≤10PPM.

[0035] This process processes the products of each work section, or recycles them, or produces by-products, or discharges them after testing to meet the standards, with zero wastewater discharge and valuable metal elements recycled as resources. The products are mainly low in oil, water-insoluble matter and magnetic foreign matter, and the impurities comply with the requirements of ROHS, REACH and HF directives. They can be used as precursor raw materials for high-performance lithium-ion power batteries. This is a clean production process with very significant economic benefits and environmental value.

[0036] Example 1

[0037] A method for producing high-performance lithium-ion power batteries using cobalt sulfate comprises the following steps:

[0038] (1) adding distilled water, industrial water and crude cobalt hydroxide into a slurry tank at a solid-liquid ratio of 1:1.6, and stirring to obtain a slurry;

[0039] (2) The slurry was pumped into the leaching tank, and 98% sulfuric acid was first added and the pH was controlled to 1.0. The reaction temperature was 52°C, and the acid leaching reaction was carried out for 0.5h. Then, 27.5% hydrogen peroxide was added for reduction leaching. The unit consumption of hydrogen peroxide was controlled at 0.55t / t. If the leaching reaction was not complete, a small amount of sodium sulfite was added. After the leaching was completed, a filter press was performed to obtain a leaching residue and a leaching filtrate. The Co content in the leaching liquid was 66.8g / l. The leaching residue was countercurrent washed three times, and the filtrate after washing was returned to the leaching step. The toxicity of the washed filter residue was detected to be 0.056%;

[0040] (3) Analysis of pH and Fe in leachate 2+ Concentration, heating 53℃, based on Fe 2+ Add hydrogen peroxide to Fe 2+ Oxidized to Fe 3+ Then, add the neutralizing agent ammonium bicarbonate or the crude cobalt hydroxide slurry prepared in step (1), adjust the pH to 3.5 to carry out precipitation reaction, react for 1 hour, and filter press after precipitation to obtain iron removal slag and iron removal liquid, Fe 全 <0.03 g / l, the iron slag is returned to the leaching section of step (2);

[0041] (4) The pH of the solution after iron removal was adjusted to 2.5, and impurities were removed by extraction with P204 (P204 concentration 25%, sulfonated kerosene concentration 75%). P204 was saponified with ammonia water, and the conversion rate was controlled at 62%. The P204 raffinate was separated from cobalt and nickel and magnesium by P507. P507 was saponified with ammonia water, and the conversion rate was controlled at 60%. The organic phase loaded with P507 was stripped with 4.0 mol / l sulfuric acid to obtain a cobalt sulfate solution with the contents of Co: 123 g / l; Ni: 0.002 g / l; Na: 0.003 g / l; Cu: 0.002 g / l; Fe: 0.002 g / l; Cr: 0.001 g / l; Cl: 0.03 g / l; Zn: 0.001 g / l; Cd: 0.002 g / l; Mg: 0.004 g / l; Ca: 0.005 g / l.

[0042] (5) The P507 raffinate is subjected to ZGD905 ion exchange resin to remove heavy metals such as nickel, cobalt, and copper, making Ni: 0.3 mg / l, Co: 0.2 mg / l, and Cu: 0.3 mg / l; then it is separated by a secondary reverse osmosis membrane, and the secondary reverse osmosis membrane concentration ratio is 4.8:1. The membrane separation water contains 10 mg / l of salt, and then enters the MVR evaporation crystallization to produce ammonium magnesium sulfate. The evaporation temperature is 82°C, and the heat exchanger pressure is 520 mbar. When the evaporation reaches a saturated solution, the material is discharged, and the distilled water is returned to the slurry section of step (1), and zero wastewater discharge is achieved;

[0043] (6) Graphene is degreased with cobalt sulfate solution, the oil content is 8 mg / l, and demagnetized with a demagnetizer, the magnetic foreign matter is 8 PPb, and the magnetic force of the magnetic rod is 13000 Gs;

[0044] (7) After demagnetization, the cobalt sulfate solution was mixed with the evaporation mother liquor and then subjected to MVR evaporation crystallization. Before evaporation, the cobalt sulfate solution contained Co: 132 g / L; Fe: 0.002 g / L; Cu: 0.002 g / L; Ca: 0.03 g / L; Mn: 0.002 g / L; Mg: 0.005 g / L; Na: 0.02 g / L; Cl: 0.3 g / L; Pb: 0.003 g / L; Cd: 0.02 g / L, and oil content: 3.36 mg / L. The feed flow rate of MVR evaporation crystallization was 6 m3 / h, the feed temperature was 65°C, the compressor temperature difference of MVR evaporator for normal evaporation was 8°C, the heat exchanger pressure was 450 mbar, and the evaporation density was 1.498 g / cm 3 Time discharging;

[0045] (8) The evaporated cobalt sulfate concentrate is poured into a crystallization kettle for cooling and crystallization. After cooling to 27°C, centrifugation is started. The centrifuged mother liquor is subjected to precision filtration (1 μm filter element) and graphene deoiling. After the mother liquor oil content reaches 5 mg / l, it is returned to the MVR evaporation and crystallization step for further evaporation and crystallization. The centrifuged material is cobalt sulfate, which is packaged after being placed for 2 hours. The obtained high-performance lithium-ion power battery uses cobalt sulfate, CO: 20.55%; Ni: 0.0001%; ​​Fe: 0.00023%; Cu: 0.0001%; ​​Ca: 0.00028%; Mg: 0.00037%; Cl: 0.0 02%; Cd: 0.00035%; Cr: 0.00015%; Na: 0.00038%; Mn: 0.0001%; ​​Pb: 0.00035%; Zn: 0.0001%, As: 0.0001%, Hg: 0.0001%; ​​Al: 0.0001%; ​​Si: 0.0001%; ​​Li: 0.0001%, K: 0.0001%; ​​F: 0.0001%; ​​Water insoluble matter 0.002%; pH: 5.8; TOC: 0.0001%; ​​Magnetic foreign matter 38PPb, oil content 1.285PPM.

[0046] Example 2

[0047] A method for producing high-performance lithium-ion power batteries using cobalt sulfate comprises the following steps:

[0048] (1) adding distilled water, industrial water and crude cobalt hydroxide into a slurry tank at a solid-liquid ratio of 1:1.90, and stirring to obtain a slurry;

[0049] (2) The slurry is pumped into the leaching tank, and 98% sulfuric acid is first added and the pH is controlled to 1.0. The reaction temperature is 55°C, and the acid leaching reaction is carried out for 0.5h. Then, 27.5% hydrogen peroxide is added for reduction leaching. The unit consumption of hydrogen peroxide is controlled at 0.5t / t. If the leaching reaction is not complete, a small amount of sodium sulfite is added. After the leaching is completed, a filter press is performed to obtain a leaching residue and a leaching filtrate. The Co content in the leaching liquid is 78.2g / l. The leaching residue is countercurrent washed three times, and the filtrate after washing is returned to the leaching step. The toxicity of the washed filter residue is detected to be 0.05%;

[0050] (3) Analysis of pH and Fe in leachate 2+ Concentration, heated to 50°C, based on Fe 2+ Add oxidants such as hydrogen peroxide, sodium hypochlorite, and sodium chlorate to Fe 2+ Oxidized to Fe 3+ Then add the neutralizing agent crude cobalt hydroxide slurry or ammonium bicarbonate to adjust the pH to 3.7 for precipitation reaction, react for 1 hour, and filter press to obtain iron removal slag and iron removal liquid, Fe 全 <0.05g / l, the iron slag is returned to the leaching section of step (2);

[0051] (4) The pH of the solution after iron removal was adjusted to 3.2, and impurities were removed by extraction with P204 (P204 concentration 24%, sulfonated kerosene concentration 76%). P204 was saponified with ammonia water, and the conversion rate was controlled at 60%. The P204 raffinate was separated from cobalt and nickel and magnesium by P507. P507 was saponified with ammonia water, and the conversion rate was controlled at 64%. The organic phase loaded with P507 was stripped with 4.4 mol / l sulfuric acid to obtain a cobalt sulfate solution with the contents of Co: 128 g / l; Ni: 0.002 g / l; Na: 0.004 g / l; Cu: 0.002 g / l; Fe: 0.002 g / l; Cr: 0.002 g / l; Cl: 0.03 g / l; Zn: 0.0008 g / l; Cd: 0.002 g / l; Mg: 0.003 g / l; Ca: 0.005 g / l.

[0052] (5) P507 raffinate is treated with ZGD905 ion exchange resin to remove heavy metals such as nickel, cobalt, and copper, making Ni: 0.3 mg / l, Co: 0.3 mg / l, and Cu: 0.3 mg / l; then it is separated by a secondary reverse osmosis membrane, and the secondary reverse osmosis membrane concentration ratio is 5.8:1. The membrane separation water contains 12 mg / l of salt, and then enters the MVR evaporation crystallization to produce ammonium magnesium sulfate. The evaporation temperature is 88°C, the heat exchanger pressure is 520 mbar, and the material is discharged when the evaporation reaches a saturated solution. The distilled water returns to the slurry section of step (1), and the wastewater is discharged zero;

[0053] (6) Graphene was deoiled with cobalt sulfate solution, the oil content was 7.8 mg / l, and demagnetized with a demagnetizer, the magnetic foreign matter was 16 PPb, and the magnetic force of the magnetic rod was 20000 Gs;

[0054] (7) After demagnetization, the cobalt sulfate solution was mixed with the evaporation mother liquor and then subjected to MVR evaporation crystallization. Before evaporation, the cobalt sulfate solution contained Co: 138 g / L; Fe: 0.004 g / L; Cu: 0.006 g / L; Ca: 0.05 g / L; Mn: 0.004 g / L; Mg: 0.005 g / L; Na: 0.01 g / L; Cl: 0.5 g / L; Pb: 0.004 g / L; Cd: 0.01 g / L, and the oil content was 7.69 mg / L. The feed flow rate of MVR evaporation crystallization was 12 m 3 / h, feed temperature is 78℃, compressor temperature difference of normal evaporation of MVR evaporator is 10℃, heat exchanger pressure is 550mbar, evaporation density is 1.518g / cm 3 Time discharging;

[0055] (8) The evaporated cobalt sulfate concentrate is poured into a crystallization kettle for cooling and crystallization. After cooling to 27°C, centrifugation is started. The centrifuged mother liquor is subjected to precision filtration (1 μm filter element) and graphene deoiling. After the mother liquor oil content reaches 7.1 mg / l, it is returned to the MVR evaporation and crystallization step for further evaporation and crystallization. The centrifuged material is cobalt sulfate, which is packaged after being placed for 2 hours. The obtained high-performance lithium-ion power battery uses cobalt sulfate, CO: 20.58%; Ni: 0.00011%; Fe: 0.00033%; Cu: 0.00025% ;Ca: 0.00043%; Mg: 0.00051%; Cl: 0.002%; Cd: 0.00035%; Cr: 0.00015%; Na: 0.00038%; Mn: 0.0001%; ​​Pb: 0.00035%; Zn: 0.0001%, As: 0.0001%, Hg: 0.0001%; ​​Al: 0.0001%; ​​Si: 0.0001%; ​​Li: 0.0001%, K: 0.0001%; ​​F: 0.0002%; Water insoluble matter 0.002%; pH: 5.3; TOC: 0.0003%; Magnetic foreign matter 36PPb, oil content 2.356PPM.

[0056] Example 3

[0057] A method for producing high-performance lithium-ion power batteries using cobalt sulfate comprises the following steps:

[0058] (1) adding distilled water, industrial water and crude cobalt hydroxide into a slurry tank at a solid-liquid ratio of 1:1.7, and stirring to obtain a slurry;

[0059] (2) The slurry is pumped into the leaching tank, and 98% sulfuric acid is first added and the pH is controlled to 1.2. The reaction temperature is 58°C, and the acid leaching reaction is carried out for 0.8h. Then, 27.5% hydrogen peroxide is added for reduction leaching. The unit consumption of hydrogen peroxide is controlled at 0.55t / t. If the leaching reaction is not complete, a small amount of sodium sulfite is added. After the leaching is completed, a filter press is performed to obtain a leaching residue and a leaching filtrate. The Co content in the leaching liquid is 72.5g / l. The leaching residue is countercurrent washed three times, and the filtrate after washing is returned to the leaching step. The toxicity of the filter residue after washing is detected to be 0.03%;

[0060] (3) Analysis of pH and Fe in leachate 2+ Concentration, heated to 50°C, based on Fe 2+ Add oxidants such as hydrogen peroxide, sodium hypochlorite, and sodium chlorate to Fe 2+ Oxidized to Fe 3+ Then add the neutralizing agent crude cobalt hydroxide slurry or ammonium bicarbonate to adjust the pH to 3.8 for precipitation reaction, react for 1 hour, and filter press to obtain iron removal slag and iron removal liquid, Fe 全 <0.05g / l, the iron slag is returned to the leaching section of step (2);

[0061] (4) The pH of the solution after iron removal was adjusted to 3.5, and impurities were removed by extraction with P204 (P204 concentration 25%, sulfonated kerosene concentration 75%). P204 was saponified with ammonia water, and the biodegradation rate was controlled at 63%. The P204 raffinate was separated from cobalt and nickel and magnesium by extraction with P507. P507 was saponified with ammonia water, and the biodegradation rate was controlled at 64%. The organic phase loaded with P507 was stripped with 4.2 mol / l sulfuric acid to obtain a cobalt sulfate solution with Co: 124 g / l; Ni: 0.003 g / l; Na: 0.002 g / l; Cu: 0.002 g / l; Fe: 0.001 g / l; Cr: 0.001 g / l; Cl: 0.03 g / l; Zn: 0.001 g / l; Cd: 0.002 g / l; Mg: 0.004 g / l; Ca: 0.005 g / l;

[0062] (5) The P507 raffinate is subjected to ZGD905 ion exchange resin to remove heavy metals such as nickel, cobalt, and copper, making Ni: 0.2 mg / l, Co: 0.3 mg / l, and Cu: 0.3 mg / l; then it is separated by a secondary reverse osmosis membrane, and the secondary reverse osmosis membrane concentration ratio is 5.1:1. The membrane separation water contains salt: 10 mg / l, and then enters the MVR evaporation crystallization to produce ammonium magnesium sulfate. The evaporation temperature is 85°C and the heat exchanger pressure is 510 mbar. When the evaporation reaches a saturated solution, the material is discharged, and the distilled water is returned to the slurry section of step (1), and zero wastewater discharge is achieved;

[0063] (6) Graphene was deoiled with cobalt sulfate solution, the oil content was 5.672 mg / l, and demagnetized with a demagnetizer, the magnetic foreign matter was 11 PPb, and the magnetic force of the magnetic rod was 15000 Gs;

[0064] (7) After demagnetization, the cobalt sulfate solution was mixed with the evaporation mother liquor and then subjected to MVR evaporation crystallization. Before evaporation, the cobalt sulfate solution contained Co: 133 g / L; Fe: 0.002 g / L; Cu: 0.005 g / L; Ca: 0.05 g / L; Mn: 0.004 g / L; Mg: 0.004 g / L; Na: 0.02 g / L; Cl: 0.4 g / L; Pb: 0.003 g / L; Cd: 0.02 g / L, and oil content: 5.8 mg / L. The feed flow rate of MVR evaporation crystallization was 12 m 3 / h, feed temperature is 78℃, compressor temperature difference of normal evaporation of MVR evaporator is 8℃, heat exchanger pressure is 560mbar, evaporation density is 1.509g / cm 3 Time discharging;

[0065] (8) The evaporated cobalt sulfate concentrate is poured into a crystallization kettle for cooling and crystallization. After cooling to 30°C, centrifugation is started. The centrifuged mother liquor is subjected to precision filtration (1 μm filter element) and graphene deoiling. After the mother liquor oil content reaches 4.8 mg / l, it is returned to the MVR evaporation and crystallization step for further evaporation and crystallization. The centrifuged material is cobalt sulfate, which is packaged after being placed for 2 hours. The obtained high-performance lithium-ion power battery uses cobalt sulfate, CO: 20.56%; Ni: 0.0001%; ​​Fe: 0.00025%; Cu: 0.0001%; ​​Ca: 0.00028%; Mg: 0.00047%; Cl: 0.002%; Cd: 0.00035%; Cr: 0.00027%; Na: 0.00028%; Mn: 0.0001%; ​​Pb: 0.00032%; Zn: 0.0001%, As: 0.0001%, Hg: 0.0001%; ​​Al: 0.0001%; ​​Si: 0.0001%; ​​Li: 0.0001%, K: 0.0001%; ​​F: 0.0001%; ​​Water insoluble matter 0.002%; pH: 5.5; TOC: 0.0005%; Magnetic foreign matter 24PPb, oil content 1.618PPM.

[0066] Finally, it should be noted that the above preferred embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail through the above preferred embodiments, those skilled in the art should understand that various changes can be made in form and details without departing from the scope defined by the claims of the present invention.

Claims

1. A method for producing high-performance lithium-ion power batteries using cobalt sulfate, characterized in that: The steps include: (1) Add distilled water, industrial water and crude cobalt hydroxide into the slurry tank and stir to obtain a slurry with a solid-liquid ratio of 1:1.5-2; (2) The slurry is pumped into the leaching tank, sulfuric acid is first added and the pH is controlled to carry out acid leaching reaction, and then hydrogen peroxide is added for reduction leaching. If the leaching reaction is not complete, a small amount of sodium sulfite is added. After the leaching is completed, filter pressing is performed to obtain leaching residue and leaching filtrate. The leaching residue is subjected to three countercurrent washings, and the filtrate after washing is returned to the leaching step. The washed filter residue is sent out for treatment and toxicity detection. The leaching acid is 98% sulfuric acid. The pH is controlled at 1.0-1.5 during the acid leaching reaction, the reaction temperature is 50-60°C, and the reaction time is 0.5-1h. The reducing agent for reduction leaching is 27.5% hydrogen peroxide, and the unit consumption of hydrogen peroxide is controlled at 0.5-0.6t / t. The Co in the leaching solution is 60-80g / l, and the total toxic substances in the leaching residue is less than 0.1%; (3) Analysis of pH and Fe in leachate 2+ Concentration, based on Fe 2+ Add oxidants such as hydrogen peroxide, sodium hypochlorite, and sodium chlorate to Fe 2+ Oxidized to Fe 3+ Then, add the neutralizing agent ammonium bicarbonate or the crude cobalt hydroxide slurry prepared in step (1), adjust the pH to carry out precipitation reaction, filter press after precipitation to obtain iron removal slag and iron removal liquid, the iron removal slag returns to the leaching section of step (2), the temperature of the hydrogen peroxide and sodium hypochlorite oxidation reaction is 50-60°C, the pH of the cobalt hydroxide slurry and ammonium bicarbonate neutralization reaction is adjusted to 3.0-3.8, the reaction is carried out for 0.5-1h, and after the reaction, the total Fe content of the solution is <0.1g / l; (4) The pH of the solution after iron removal is adjusted, and impurities are removed by extraction with P204. P204 is saponified with ammonia water. The P204 raffinate is separated from cobalt and nickel and magnesium by P507. P507 is saponified with ammonia water. The organic phase loaded with P507 is stripped with sulfuric acid to obtain a cobalt sulfate solution. The pH of the solution after iron removal is adjusted to 2.5-3.5, the concentration of P204 is 24-28%, and it is diluted with sulfonated kerosene with a concentration of 72-76%. P204 is saponified with 20-25% ammonia water, and the saponification rate is controlled to 60-65%. The saponification rate of P507 is controlled to 60-65%, and the concentration of sulfuric acid stripping is 4.0-4.5 mol / l; (5) The P507 raffinate is subjected to ion exchange to remove impurities, secondary reverse osmosis membrane separation and evaporation crystallization to produce ammonium magnesium sulfate, and the distilled water evaporated from the P507 raffinate is returned to the slurry process in step (1), with zero wastewater discharge; (6) Graphene is degreased with cobalt sulfate solution and demagnetized with a demagnetizer. The cobalt sulfate solution is degreased to an oil content of <10 mg / l and demagnetized to a magnetic foreign body of <20 PPb. The magnetic force of the demagnetizer is >12000 Gs. (7) After demagnetization, the cobalt sulfate solution is mixed with the evaporation mother liquor and then subjected to MVR evaporation crystallization. The feed flow rate of MVR evaporation crystallization is 6-15m3 / h, the feed temperature is 65-80°C, the compressor temperature difference of the MVR evaporator is ±12°C for normal evaporation, the heat exchanger pressure is 350-600mbar, and the evaporation density is 1.49-1.52g / cm3 before discharging; (8) The evaporated cobalt sulfate concentrate is poured into a crystallization kettle for cooling and crystallization. After cooling and crystallization, centrifugation is started. The centrifuged mother liquor is finely filtered and graphene deoiled before returning to the MVR evaporation and crystallization step to continue evaporation and crystallization. The centrifuged material is cobalt sulfate. After cooling and crystallization to 27-35°C, centrifugation is started. The mother liquor is finely filtered using a 1μm filter element. The mother liquor is deoiled to an oil content of ≤8mg / l. The centrifuged cobalt sulfate is placed for 2-4h before packaging.

2. The method for producing high-performance lithium-ion power batteries using cobalt sulfate according to claim 1, characterized in that: In step (5), the P507 raffinate is evaporated and crystallized to produce ammonium magnesium sulfate. First, the P507 raffinate is subjected to ZGD905 ion exchange resin to remove heavy metals such as nickel, cobalt and copper, so that Ni is less than 0.5 mg / l, Co is less than 0.5 mg / l, and Cu is less than 0.5 mg / l; then reverse osmosis separation is performed, and the secondary reverse osmosis membrane concentration ratio is 4-6:1, and the salt content of the membrane separation purified water is less than 15 mg / l. Then, it enters MVR evaporation and crystallization, the evaporation temperature is 75-90°C, the heat exchanger pressure is 450-600 mbar, and the material is discharged when evaporation to a saturated solution.

Citation Information

Patent Citations

  • Method for treating wastewater containing high-concentration organic matters and inorganic salts

    CN104058540A

  • Co-production process of cobalt sulfate and cobalt chloride

    CN113044889A

  • Process for Leaching Lateritic Ore at Atmospheric Pressure

    US20080271571A1